Unraveling Communication Barriers among Apathetic Students in Media Writing - Surendra, Gilang; Laily, Hamidah Izzatu; Telaumbanua, Yohannes (Politeknik Negeri Bengkalis, 2024)
This qualitative research explores the communication barriers that contribute to apathy among students in the